KAJIAN TEOLOGIS DAN PRAKTIS: PENERAPAN KEPEMIMPINAN TUHAN YESUS BAGI TERANG DUNIA BERDASARKAN FILIPI 2:5-8 - Pinondang Siregar; Hadi, Tan (STT Ekklesia Pontianak, 2025)
Abstract: This study thoroughly examines the leadership model of Jesus Christ, which is rooted in the theological principles found in Philippians 2:5-8. The study then formulates practical guidelines for contemporary leadership based on these principles. Often referred to as the